2009
DOI: 10.1159/000210101
|View full text |Cite
|
Sign up to set email alerts
|

Peptic Esophageal Stricture: Medical Treatment

Abstract: Peptic esophageal stricture as a consequence of gastroesophageal reflux disease is the most frequent among benign esophageal strictures. The incidence is low and has been decreasing since the 1990s with a parallel increase in proton pump inhibitor use. Dysphagia is a common symptom: accurate diagnostic procedures (barium esophagogram, upper endoscopy with biopsies) have to be performed to exclude malignant causes first. Medical (acid-suppressive) therapy, endoscopic dilation and surgical intervention are the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 72 publications
0
15
0
2
Order By: Relevance
“…Up to 70% of all benign esophageal strictures in the US were caused by reflux disease (74,96). With the emergence of PPIs in the 1990s, the incidence of esophageal strictures decreased dramatically (26,107).…”
Section: Impact Of Inflammatory Mediators On Esophageal Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 70% of all benign esophageal strictures in the US were caused by reflux disease (74,96). With the emergence of PPIs in the 1990s, the incidence of esophageal strictures decreased dramatically (26,107).…”
Section: Impact Of Inflammatory Mediators On Esophageal Fibrosismentioning
confidence: 99%
“…The pathophysiology of fibrosis in the esophagus is unclear (96,101). It is believed that fibrosis develops after epithelial injury, causing proliferation and activation of resident fibroblasts and deposition of ECM, as a response to tissue damage caused by acid peptic injury.…”
Section: Impact Of Inflammatory Mediators On Esophageal Fibrosismentioning
confidence: 99%
“…Recent epidemiological data have indicated that treatment with PPI is effective in prevention of oesophageal peptic strictures in general when treated with PPI for a period of at least 3 months [2,3]. In patients with peptic oesophageal strictures the healing of coexisting esophagitis is crucial and PPI treatment has been suggested to reduce dilatation frequency and to provide symptom relief [4].…”
Section: Introductionmentioning
confidence: 99%
“…In Europe and North America, benign OS is commonly caused by recurrent peptic and to a lesser degree by non-peptic pathology such as corrosive injury, eosinophilicoesophagitis, post-surgery, and trauma [9,10]. In this cohort of patients, GORD was the main associated risk factor for benign OS.…”
Section: Discussionmentioning
confidence: 96%